Why voters do not throw the rascals out?- A conceptual framework for analysing electoral punishment of corruption - Sousa, L. (2014)
One of the intriguing phenomena in democracy is the fact that politicians involved in, accused of or condemned for corruption in a court of law get re-elected by their constituents. In some cases, corruption does not seem to negatively affect the development of political careers. In this introductory article, we try to develop a multidimensional framework for analysing electoral punishment of corruption. First, we will look into various studies on electoral punishment and highlight their advancements and shortcomings. Then, we will propose a more dynamic account of electoral punishment of corruption that takes into account individual as well as macro level explanations. Finally, we will disaggregate these two analytical dimensions into various explanatory factors.